Piecing me together eaudiobook - Watson, Renée (Recorded Books Inc., 2018)
Newbery Honor and Coretta Scott King Author Award Winner New York Times bestseller Acclaimed author Renee Watson offers a powerful story about a girl striving for success in a world that too often seems like it's trying to break her. Jade believes she must get out of her poor neighborhood if she's ever going to succeed. Her mother tells her to take advantage of every opportunity that comes her way. And Jade has: every day she rides the bus away from her friends and to the private school where she feels like an outsider, but where she has plenty of opportunities. But some opportunities she doesn't really welcome, like an invitation to join Women to Women, a mentorship program for "at-risk" girls. Just because her mentor is black and graduated from the same high school doesn't mean she understands where Jade is coming from. She's tired of being singled out as someone who needs help, someone people want to fix. Jade wants to speak, to create, to express her joys and sorrows, her pain and her hope. Maybe there are some things she could show other women about understanding the world and finding ways to be real, to make a difference. NPR's Best Books of 2017 A 2017 New York Public Library Best Teen Book of the Year Chicago Public Library's Best Books of 2017 A School Library Journal Best Book of 2017 Kirkus Reviews' Best Teen Books of 2017 2018 Josette Frank Award Winner